Development of Three Psychology Sub-Disciplines Over the Past 30 Years: A Citation Analysis. Issue 2 (June 2023) - Singer, Susanne
At the end of the last century, there was a debate about whether cognitive psychology had superseded behavioral psychology and psychoanalysis, and the question was raised of whether the latter two might even be dead. The aim of this study was to investigate how these sub-disciplines have developed since then. The citation count, Journal Impact Factor (JIF), and Immediacy Index of four leading journals from each sub-discipline were abstracted for the years 1998, 2008, and 2018. Trends were analyzed using joinpoint regression analysis. The average number of times each sub-discipline's journals were cited increased between 1988 and 2018. The cognitive journals' JIF increased slightly, the behavioral journals' doubled, and the psychoanalytic journals' remained at the same level. The average annual percentage change for citations to the International Journal of Psychoanalysis showed that the number of citations statistically significantly increased over the years. This was also the case for the Journal of Applied Behavior Analysis . Its JIF trend changed at one point: it decreased up through 2006, after which it increased. Citations to Cognitive Psychology also increased over time, while there was no evidence that its JIF changed. This shows that all three sub-disciplines are still alive and relevant.